Emotions, technology, and design - Tettegah, Sharon Y.; Noble, Safiya Umoja (Emotions and technology, 2016)
Emotional design explicitly addresses the emotional relationship between the objects and the subjects of design-in this book, the objects are technologies, and the subjects are technology users. The first section delves into the philosophy and theory of emotional design to provide a foundation for the rest of the book, which goes on to discuss emotional design principles, the design and use of emoticons, and then intelligent agents in a variety of settings. A conclusion chapter covers future research and directions. Emotions, Technology, and Design provides a thorough look at how technology design affects emotions and how to use that understanding to in practical applications